Clinical Exercise Testing 2002
DOI: 10.1159/000062206
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Respiratory System Responses and Limitations to Exercise

Abstract: The design and dimensions of the healthy pulmonary system are nearly perfect to meet the considerable demands on O 2 transport and CO 2 elimination imposed by physical exercise. In our chapter, we briefly describe the features of the nervous system pathways and the structure of the airways, lung surface area and respiratory muscles which ensure both the completeness of gas exchange at the level of alveolar gas, pulmonary capillaries and arterial blood and the high level of mechanical efficiency with which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
5
0
1
Order By: Relevance
“…This ventilatory pattern, well described in endurance athletes, offers less expenditure of ventilation in dead space and, therefore, minor work of respiratory muscles (Clark et al 1983;Johnson et al 1992). This pattern could be related to a reduced chemoreceptor sensitivity associated with a lower dyspnoea feeling (Rodman et al 2002;Takano et al 1997). Harms et al showed that minor tiredness in respiratory muscles, which can be experimentally obtained by mechanical unloading of these muscles, allows for a reduction of respiratory muscles _ VO 2 and blood flow and that this phenomenon is associated with more than 10% leg blood flow increase (Harms et al 1995;Harms et al 1997).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This ventilatory pattern, well described in endurance athletes, offers less expenditure of ventilation in dead space and, therefore, minor work of respiratory muscles (Clark et al 1983;Johnson et al 1992). This pattern could be related to a reduced chemoreceptor sensitivity associated with a lower dyspnoea feeling (Rodman et al 2002;Takano et al 1997). Harms et al showed that minor tiredness in respiratory muscles, which can be experimentally obtained by mechanical unloading of these muscles, allows for a reduction of respiratory muscles _ VO 2 and blood flow and that this phenomenon is associated with more than 10% leg blood flow increase (Harms et al 1995;Harms et al 1997).…”
Section: Discussionmentioning
confidence: 75%
“…Excessive alveolar to arterial O 2 pressure (DP A-a O 2 ) difference, abnormal increases in arterial CO 2 pressure (P a CO 2 ) and haemoglobin desaturation have been demonstrated (Dempsey and Wagner 1999;Durand et al 2000;Rodman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Bu egzersizden sonra kişi aralıklı olarak birçok defa (örneğin 1,3 [6]. Yapılan çalışmalarda metakolin duyarlılık testi bronş aşırı duyarlılığını değerlendirmede daha üstün olduğu gösterilmiştir [22].…”
Section: Egzersiz Ile Indüklenen Bronkospazm (Ei̇b) Testiunclassified
“…In the cardiological context, CPET is a well recognized method to diagnose and/or investigate cardiovascular dysfunction (e.g., myocardial ischemia, chronic heart failure) [ 10 , 13 ]. With respect to lung diseases, the goal of CPET is the identification of physiopathological determinants of respiratory dysfunction as well as matching the pattern of the abnormality with the particular sites of the system involved, thus clarifying the clinical picture and possibly narrowing the differential diagnosis [ 14 , 15 ]. Furthermore, the physiological link between respiratory and cardiovascular functions might cause the changes in one system to influence the performance of the other.…”
Section: Discussionmentioning
confidence: 99%